A comprehensive approach to the restoration of historic gardens - Fatsar, Kristóf (4D Journal of Landscape Architecture and Garden Art, 2009)
To fully succeed at garden restoration, one must first of all conduct a thorough, scholarly research survey of the given site. In addition, field surveys should be carried out simultaneously using archivál evidence. This field work relies on historic base maps which are to be produced by laying period maps over a digital, cadastral map throughthe process of rubber sheeting. This method can only be carried out with sophisticated geographical information system (GIS) software, because simple overlaying cannot cope with some of the significant errors of historic mapping.
Keywords: Eszterháza; Csákvár; historic gardens